\(3x(x-l)=2+6\)

Apply the distributive property \(3x^{2}-3x=x+6\)

Subtract «+ 6 from each side \(3x^{2}-3x—x-6=0\)

\(3x^{2}-4x-6=0\)

By the quadratic formula \(x=\frac{-(-4)\pm \sqrt{(-4)^2-4(3)(-6)}}{2(3)}\)

\(x=\frac{4\pm\sqrt88}6=\frac{4\pm\sqrt4*22}6)\)

\(x=\frac{4}{6}\pm\frac{2\sqrt{22}}6\)

\(x=\frac{2}{3}\pm \frac{\sqrt{22}}{3}\)

Apply the distributive property \(3x^{2}-3x=x+6\)

Subtract «+ 6 from each side \(3x^{2}-3x—x-6=0\)

\(3x^{2}-4x-6=0\)

By the quadratic formula \(x=\frac{-(-4)\pm \sqrt{(-4)^2-4(3)(-6)}}{2(3)}\)

\(x=\frac{4\pm\sqrt88}6=\frac{4\pm\sqrt4*22}6)\)

\(x=\frac{4}{6}\pm\frac{2\sqrt{22}}6\)

\(x=\frac{2}{3}\pm \frac{\sqrt{22}}{3}\)